1958
DOI: 10.1071/bt9580059
|View full text |Cite
|
Sign up to set email alerts
|

Dark Island heath (Ninety-mile Plain, South Australia). VI. Pyric succession: changes in composition, coverage, dry weight, and mineral nutrient status

Abstract: The dynamic changes in the composition, dry weight, and mineral nutrient status of heath following fire have been investigated. The overall growth (dry weightltime) curve for the aerial organs of the heath is essentially exponential. Soil moisture is conserved by burning and, provided climatic conditions are favourable, regeneration of all species is rapid. Annual species are rare and are found only in the first year after a fire. Many species are fire-resistant and regenerate rapidly from buriedperennating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(98 citation statements)
references
References 0 publications
7
85
1
Order By: Relevance
“…As succession proceeds and the canopy closes, herbaceous vegetation is either restricted to small openings, as in the case of phryganic ecosystems and to a lesser degree in coniferous forests, or remains dormaqt in the soil in the form of seeds waiting for the next fire to come (Arianoutsou 1979;Kazanis and Arianoutsou 1996). Similar results have been reported by Specht et al (1958) for heath stands in Australia, Bond (1980) for fynbos stands in South Africa, Horton and Kraebel (1955) for chaparral, Espirito- Santo et al (1993) for sclerophyllous formations in Portugal, Faraco et al (1993) for pine woodlands and shrublands in Spain, Mazzoleni andPizzolongo (1990), De Lillis andTesti (1990), Lucchesi and Giovannini (1993) for similar communities in Italy.…”
Section: Post-fire Successionsupporting
confidence: 64%
See 2 more Smart Citations
“…As succession proceeds and the canopy closes, herbaceous vegetation is either restricted to small openings, as in the case of phryganic ecosystems and to a lesser degree in coniferous forests, or remains dormaqt in the soil in the form of seeds waiting for the next fire to come (Arianoutsou 1979;Kazanis and Arianoutsou 1996). Similar results have been reported by Specht et al (1958) for heath stands in Australia, Bond (1980) for fynbos stands in South Africa, Horton and Kraebel (1955) for chaparral, Espirito- Santo et al (1993) for sclerophyllous formations in Portugal, Faraco et al (1993) for pine woodlands and shrublands in Spain, Mazzoleni andPizzolongo (1990), De Lillis andTesti (1990), Lucchesi and Giovannini (1993) for similar communities in Italy.…”
Section: Post-fire Successionsupporting
confidence: 64%
“…Very few data are available for either Mediterranean-type ecosystems. Specht et al (1958) showed accelerating fruit production from about nine years to between 20 and 25, with some decline afterwards. Bond (1980), however, did not find a similar trend in fynbos.…”
Section: Life Span and Fecundity Of Seeding Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gyrostemon australasicus) or regenerate from adaptive organs such as lignotubers (e.g. A. pusilla) (Specht et al 1958;Gill 1981). Such regeneration provides abundant shoot growth and soft foliage upon which phytophagous insects in Ngarkat are dependent (Edmonds and Specht 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Such regeneration provides abundant shoot growth and soft foliage upon which phytophagous insects in Ngarkat are dependent (Edmonds and Specht 1979). Even 10 years after fire, Ngarkat heaths are still relatively productive habitats in comparison with mature heaths (Specht et al 1958). With age, however, many seeding shrubs present after the fire senesce (Ward and Paton 2004), decreasing habitat productivity and the diversity of shrubs present in the mature heaths (Specht et al 1958).…”
Section: Discussionmentioning
confidence: 99%